Representing Reality in Court: Power and Persuasion in Trial Discourse, as exemplified in The People v. Orenthal James Simpson - Cotterill, Janet (International Journal of Speech, Language and the Law, 2001)
Representing Reality in Court explores the language of the US adversarialtrial process as exemplified in the infamous case of Orenthal James (OJ)Simpson. In 1995, Simpson, the all-American football hero turned actorand celebrity, was charged with the double homicide of his ex-wife and amale friend. The resulting trial lasted nine months, involved 126 witnessesand cost Los Angeles County an estimated $9 million. This thesis examinesthe trial as the site of linguistic power and persuasion, focusing on the roleplayed by linguistic and discursive choices in (re)presenting and (re)constructingthe acts and actors involved in the crime and its investigation.The data analysed represent a uniquely complete resource, drawing on theextended legal process from Simpson’s post-arrest interview through tothe 6.2 million word trial itself and beyond. The insights gained from thisanalysis are supplemented by media reports of the trial as well as post-trialinterviews with jurors and books written by them. The result is a multidimensionaland multiperspectival view of the discourse of the ‘Trial of theCentury’.The thesis moves through the criminal trial process, beginning with aconsideration of the linguistic consequences of the adversarial system,which is based upon the adjudication of conflicting and competing versionsof events presented by prosecution and defence. The adversarialapproach prioritises argumentation and persuasion, with its primaryobjective a dialectic and dialogic appraisal of the evidence. In this context,the linguistic means by which the evidence is elicited and presented is ofcrucial importance.The thesis is structured around the notion of the trial as a process ofstorytelling. I analyse the effects of the constraints imposed by the law andthe legal process on witnesses’ freedom to ‘tell their own story’ in court,and explore the manipulation of time, space and perspective in the transitionfrom the ‘real world’ (real time) events of the crime to the setting ofthe courtroom. The concept of ‘audience’ is also central to the thesis. Ianalyse the types of talk which occur in the trial-by-jury process, exemplifiedin the OJ Simpson trial, and discuss the ways in which the hierarchyof the courtroom influences talk by its participants. I explore the complexitiesof audience types in the Simpson trial (involving both internaland external viewers and voyeurs) and their influence on the kinds of talkproduced in court. Finally, I examine how the presence of the jury – thetrial’s ‘silent participant’ – influences the discourse of the judge, lawyersand witnesses in the case.Next I examine the negotiation of power, knowledge and statusbetween the expert witness and the lawyer. The lawyer questioning theexpert is faced with a communicative dilemma: she/he must simultaneouslyestablish and maintain the expert status of the witness, therebyvalidating their evidence and creating credibility, but this demand must bereconciled with the conflicting need to communicate with a lay jury, whoseunderstanding of the issues and their concomitant terminology may belimited or even non-existent. In addition, the lawyer must balance establishingthe credibility of the witness with their own professional status inthe courtroom. This section analyses the layering of power and expertisein the Simpson courtroom and its delicate negotiation by means ofcomplex discursive strategies.Framing the dialogic elicitation of testimony during witness(cross)examination are the monologic opening and closing statements.The thesis goes on to consider the lexical representation of the acts andactors involved in the crime story and the role of strategic lexical choicesin constructing the prosecution and defence narrative frameworks. In ananalysis of the opening statements, I consider the lexicalization of Simpsonas a spouse abuser and the conflicting semantic prosodies and connotationsconveyed by the prosecution and defence representations of bothSimpson and his ex-wife. By studying the patterns of co-occurrence andconnotation of these particular lexical items in common usage in theCOBUILD Bank of English, I elucidate the ways in which lawyers in theSimpson case attempted to map out for the jury a persuasive semanticenvironment within which to consider the ‘mountain of evidence’ fromboth sides. In addition I explore attempts to present a persuasive summaryof the evidence during the closing arguments. Taking a further lexicallyoriented strategy – the use of metaphor – as its focus, this section of thethesis ends with a discussion of the systematic network of metaphoricalreferences used by both prosecution and defence in the closing arguments,in their attempts to conceptualize and reconceptualize Simpson (as a timebomb) and the trial process itself (as the completion of a jigsaw puzzle).The thesis, like the trial, concludes with the deliberation process andverdict. Although Californian law prohibits direct access to the jury’sdeliberations, in this case researchers do have access to the jurors’ posttrialthoughts and reflections. The interviews, journals and booksproduced by jurors about their experiences during the trial and duringdeliberation provide a fascinating ‘insider’ perspective on the Simpsontrial process. In addition to analysing the jurors’ self-observations, thisfinal section also includes the contributions of lawyers, psychologists andlinguists, all of whom have attempted to explain the sensational not-guiltyverdict. Finally, I conclude with a discussion of some of the implications ofthe Simpson trial, and its verdict, for the criminal trial-by-jury system, andwhat The People vs Orenthal James Simpson can teach us about the languageof the courtroom.